Comparison of Midterm Survivorship, Radiographic, and Clinical Outcomes of the INBONE II and Salto Talaris Total Ankle Arthroplasty Systems. Issue 4 (November 2022) - Rajan, Lavan; Cronin, Samantha; Cororaton, Agnes D.; Kim, Jaeyoung; Srikumar, Syian; Mizher, Rami; Day, Jonathan; Gagne, Oliver; Henry, Jensen K.; Deland, Jonathan T.; Demetracopoulos, Constantine A.; Ellis, Scott J.
Category: Ankle; Ankle Arthritis Introduction/Purpose: Prior studies on the INBONE II and Salto Talaris total ankle arthroplasty (TAA) systems have reported favorable outcomes for both implants. However, it is unclear whether there were significant differences in survivorship between and if this led to subsequent differences in clinical or radiographic outcomes the two. To date, no similar comparisons have been done in the literature, although it is important to understand the clinically relevant distinctions between these more recent third generation TAA systems. This retrospective study aimed to compare the midterm differences between INBONE II and Salto Talaris TAA. Methods: Between 2007 and 2015, 44 INBONE II consecutive cases and 85 Salto Talaris consecutive cases had minimum 5-year clinical and radiographic follow-up. The endpoints for survivorship were revision, defined as removal or replacement of any implant component, and reoperation, defined as a non-revision surgery. Preoperative and midterm postoperative Foot and Ankle Outcome Score (FAOS), which has been validated for ankle osteoarthritis, and radiographic measures including tibiotalar alignment (TTA) and medial distal tibial angle (MDTA) were compared. Talar inclination angle (TIA) was compared to examine subsidence and cysts were examined for osteolysis. Average midterm follow-up for these patients was 6.4 +- 1.1 (range, 5-9) years for the INBONE II group, and 7 +- 1.9 (range, 5-12.7) years for the Salto Talaris group. Results: Survivorship to revision was 97.6% (95% CI, 93.1%-100%) for the INBONE II group and 97% (95% CI, 93%-100%) for the Salto Talaris group (P = .93). Survivorship to reoperation was significantly different; 95.5% for the INBONE II and 76.4% for Salto Talaris (P = .021) (Figure 1). All FAOS improved postoperatively (P < .001), although the INBONE II had superior postoperative scores in pain (P = .01), symptoms (P = .004), and sports activity (P = .02). There were no differences between groups in postoperative radiographic alignment, despite the INBONE group having greater preoperative deformity. There was one instance of subsidence in each group and similar rates of cyst occurrence across the INBONE II (18.2%) and Salto Talaris (21.2%) groups. Conclusion: Although both implants had similar longevity and postoperative alignment, the INBONE II resulted in greater clinical improvement and fewer reoperations than the Salto Talaris at midterm follow-up. The majority of reoperations in the Salto Talaris group were due to gutter impingement. The contrasting reoperation rates between groups may be explained by differences in implant design and technique, such as rotational malpositioning of the talus and the lateral sulcus design of the Salto Talaris. Additionally, the INBONE II TAA system was able to correct deformity and improve clinical outcomes even though this cohort exhibited greater preoperative deformity.